2009
DOI: 10.1007/s12263-009-0142-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of multiple pathways involved in the maintenance of neuronal function during aging by fisetin

Abstract: Multiple factors have been implicated in the age-related declines in brain function. Thus, it is unlikely that modulating only a single factor will be effective at slowing this decline. A better approach is to identify small molecules that have multiple biological activities relevant to the maintenance of brain function. Over the last few years, we have identified an orally active, novel neuroprotective and cognition-enhancing molecule, the flavonoid fisetin. Fisetin not only has direct antioxidant activity bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 97 publications
(117 reference statements)
4
76
0
Order By: Relevance
“…(1,2) Numerous studies have reported the biological effects of fisetin on anti-tumor, (3)(4)(5)(6)(7) anti-oxidant, (8) antimetastatic, (9) anti-diabetic, (10) neuroprotective, (11) and antiaging activities. (12) Inflammation, a biological response to physical or chemical injurious stimuli, (13) is closely associated with the release of pro-inflammatory mediators such as inducible nitric oxide synthase (iNOS), nitric oxide (NO) and cyclooxygenase 2 (COX-2), (14) and proinflammatory cytokines such as interleukin (IL)-6 and tumor necrosis factor α (TNF-α). (15) The expression of these inflammation-related genes is controlled by the intracellular signaling pathways such as mitogenactivated protein kinases (MAPKs) and nuclear factor κ B (NF-κB) at both transcriptional and post-transcriptional levels.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) Numerous studies have reported the biological effects of fisetin on anti-tumor, (3)(4)(5)(6)(7) anti-oxidant, (8) antimetastatic, (9) anti-diabetic, (10) neuroprotective, (11) and antiaging activities. (12) Inflammation, a biological response to physical or chemical injurious stimuli, (13) is closely associated with the release of pro-inflammatory mediators such as inducible nitric oxide synthase (iNOS), nitric oxide (NO) and cyclooxygenase 2 (COX-2), (14) and proinflammatory cytokines such as interleukin (IL)-6 and tumor necrosis factor α (TNF-α). (15) The expression of these inflammation-related genes is controlled by the intracellular signaling pathways such as mitogenactivated protein kinases (MAPKs) and nuclear factor κ B (NF-κB) at both transcriptional and post-transcriptional levels.…”
Section: Introductionmentioning
confidence: 99%
“…Fisetin prevents neuroinflammation by suppressing activated neuroinflammatory mediators and gliosis (Ahmad et al, 2016). It has also been shown to affect multiple pathways involved in neuronal function in the process of aging (Maher, 2009). Fisetin is reported to have anti-inflammatory, and other health beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Fisetin is a potent anti-inflammatory, anti-cancer, and anti-oxidant compound (Suh et al 2008;FunakoshiTago et al 2011;Jash and Mondal 2014). Moreover, it has been demonstrated to have a neuroprotective effect and also to limit the complications of type I diabetes (Maher 2009;Maher et al 2011). Based on the molecular structure of this compound, we hypothesized that its biosynthesis should follow the general pathway of flavonol biosynthesis (Figs.…”
Section: Other Activitiesmentioning
confidence: 99%